The Impact of Digital Economy on Residents' Health: Based on the Perspective of Population Ageing - You, Zhi-Ting; Zhong, Min; Gao, Qing; Wei, Hong-Xiang; Zeng, Xi-Hao (Frontiers in Public Health, 2021)
This paper uses panel data from inland provinces of China to perform fixed effect regression and finds that the development of the digital economy has a significant promotion effect on the health of residents. After that, the population aging rate is further used as a threshold variable for threshold regression, and the relationship between the development of the digital economy and the health of residents from the perspective of aging is discussed. The empirical results show that the aging of the population will reduce the role of the digital economy in promoting residents' health. There is a non-linear single threshold effect between the development of the digital economy and residents' health indicators. In the more developed areas of my country's digital economy, when the aging rate of the population exceeds the threshold, the positive impact of the development of the digital economy on the health of the population is significantly weakened. However, there is no threshold effect in areas where the development of the digital economy is relatively backward. These asymmetric developments are closely related to economic development, historical and cultural factors, and policies formulated by the government.